Evaluation of olive oil adulteration by physical and chemical parameters - Aued-Pimentel, Sabria (1994)
In order to evaluate olive oil identity and quality characteristics fifteen analytical parameters from virgen olive oil and from its differents mixtures with soybean oil, were studied. The principal fatty acids composition, iodine value, refractive index, esqualene contents, especific extintions at 232 and 270 nm, acidity, peroxides index, the ratio of oleic to linoleic acids (O/Li) and a parameter from second derivative ultraviolet spectra (ΔK 1%/lcm 310 - 313 nm), were determined. The data were statistically treated by descriptive and principal component analysis techniques. Most of the parameters studied showed high correlation among them, as well as, a linear behaviour with adulteration level increase. The refrative index and linolenic acid contents showed to be the most sensitive parameters to discriminate olive oil adulteration with soybean oil, agreeing with the acceptable ranges given by Codex Alimentarius. Principal component analysis of parameters sets studied, were not more efficient than some individual parameters to evaluate adulteration. The evaluation of the ratio O/Li showed that this parameter can be utilized only as an indicator of olive oil adulteration, due to the variability of these fatty acids in vegetable oils.